2021
DOI: 10.3390/ijerph182111528
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Burden of Diabetes-Related Foot Disease in New South Wales, Australia: Evidence from the 45 and Up Study Survey Data Linked with Health Services Data

Abstract: Diabetes-related foot disease (DFD) is a major public health concern due to the higher risks of hospitalisation. However, estimates of the prevalence of DFD in the general population are not available in Australia. This study aims to estimate the prevalence of DFD and diabetes-related lower-extremity amputation (DLEA) among people aged 45 years and over in New South Wales (NSW), Australia. The NSW 45 and Up Study baseline survey data of 267,086 persons aged 45 years and over, linked with health services’ admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Our finding is also corroborated by the study by Zhang et al (2020), where they reported that the burden disproportionately affected males and the older aged population globally 7 . Although females in Australia have a higher life expectancy, the higher YLD burden could be due to the higher prevalence of diabetic foot complications among males for most age groups, as documented by several studies 23,31‐34 …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our finding is also corroborated by the study by Zhang et al (2020), where they reported that the burden disproportionately affected males and the older aged population globally 7 . Although females in Australia have a higher life expectancy, the higher YLD burden could be due to the higher prevalence of diabetic foot complications among males for most age groups, as documented by several studies 23,31‐34 …”
Section: Discussionsupporting
confidence: 91%
“…7 Although females in Australia have a higher life expectancy, the higher YLD burden could be due to the higher prevalence of diabetic foot complications among males for most age groups, as documented by several studies. 23,[31][32][33][34] Our study found that the number of deaths due to DFUIG was 7 per 100 000 people in 2011 among individuals aged 45 years and older. At this rate, the total number of deaths due would equate to 587 deaths due to DFUIG in Australia.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations